Seroprevalence of Brucellosis in Buffalo Worldwide and Associated Risk Factors: A Systematic Review and Meta-Analysis - Shi, Jun-Feng; Gong, Qing-Long; Zhao, Bo; Ma, Bao-Yi; Chen, Zi-Yang; Yang, Yang; Sun, Yu-Han; Wang, Qi; Leng, Xue; Zong, Ying; Li, Jian-Ming; Du, Rui (Frontiers in Veterinary Science, 2021)
Background: Brucellosis is an important zoonotic disease caused by Brucella spp. Brucellosis is widely distributed in more than 160 or 170 countries around the world, where it poses a huge threat to animal husbandry and human health. About 150 million head of water buffalo, distributed across more than 40 countries worldwide are kept for the purposes of service, milk, and meat. High incidence of Brucella spp. in buffalo has negatively affected dairy products and meat products. Results: We searched all research related to seroprevalence of brucellosis in water buffalo anywhere in the world in PubMed, Science Direct, SpringerLink, China National Knowledge Infrastructure, Wanfang Database, and VIP Chinese Journal Databases. A total of 26 articles published from 1985 to 2020 met the final selection criteria. The overall seroprevalence of buffalo brucellosis worldwide was 9.7%. The seroprevalence before 2010 (20.8%) was much higher than the seroprevalence rate from 2010 to 2020 (4.2%). Subgroup analysis by feeding mode found that the point estimate of seroprevalence in stock buffalo (11.5%) was higher than that in captive buffalo (10.6%). Subgroup analysis by farming mode found that the seroprevalence was higher in captive-bred buffalo (10.7%) than in intensively farmed buffalo (8.5). The seroprevalence in buffalo living in dry lands (6.4%) is greater than that in buffalo living in wetlands (5.1%) (P < 0.05). The seroprevalence in female buffalo (10.1%) was higher than that in male buffalo (4.4%). The seroprevalence in lactating buffalo was higher than that in buffalo of other ages (26.9%). Subgroup analysis by detection method found that the seroprevalence detected by the complement fixation test (27.3%) was much higher than that detected by other methods. Conclusion: The results of this meta-analysis showed that buffalo brucellosis infection is very common in buffalo herds around the world. Although the seroprevalence of brucellosis in buffalo and humans is relatively low, serious effects upon animal husbandry and public health make it necessary to take effective control and preventive measures to control the spread of this disease.